(untitled) (International Journal of Engineering and Computer Science, 2013)
The C programming language was derived in the early 1970s as a system implementation language for the nascent UNIX operating system. It is derived from the type-less language BCPL. The extension in standard ANSI C i.e., adding concept of classes, object, etc developed a new language known as Objective-C. After few years C adapts some features of Objective-C and a language come into existence known as C with classes, later it is known as C++. This paper studies about the languages, influence of one language to another and comparative study of the languages.